Decadal beach-dune profile monitoring along a 230-km high-energy sandy coast: Aquitaine, southwest France. (February 2022) - Nicolae Lerma, A.; Castelle, B.; Marieu, V.; Robinet, A.; Bulteau, T.; Bernon, N.; Mallet, C.
Abstract: Large-scale coastal monitoring programs are challenging to maintain over time but are necessary to understand and further predict complex coastal evolution and resilience. The 230 km-long Aquitaine coast is a high-energy meso-macrotidal coast composed of beach-dune systems showing dramatic morphological changes at seasonal and interannual scales. This study investigates the alongshore variability in beach-dune response based on a unique 11-year dataset of 41 spaced transects surveyed yearly in spring. The dataset is completed by interspersed autumn LiDAR surveys for seasonal analysis. Several beach-dune morphological descriptors are developed, such as beach-dune volume, beach width and different shoreline proxies delimiting the intertidal zone, the beach face and the dune face. The Aquitaine beach-dune system is characterised by a north-south gradient, from chronically eroding dunes backing low-elevation dissipative beaches in the north, to slowly accreting dunes backing wide beaches in the south, through a range of intermediate beach-dune states. Time- and spatially-averaged shoreline (dune foot position) trend is −0.5 m/year (erosion), with local variations ranging from −5.9 m/year to +2.1 m/year. During the 2013–2014 winter widespread erosion was observed, with the shoreline eroding by 13 m and 8 m on average along the Gironde and Landes coasts, respectively. This dataset provides insight into the timing, magnitude and spatial variability of beach-dune recovery from the outstandingly erosive 2013–2014 winter. We also show that local beach-dune volume is a good proxy for long-term shoreline trend. It is advocated that such large-scale coastal monitoring by means of single beach profiles spaced and distributed along 10–100 km of coast is a cheap and efficient approach to address coastal changes at regional scale, which can bring complementary information to aerial photographs interpretation to determine long-term shoreline evolution trend and thus contribute to support sustainable coastal management and planning. Highlights: Analysis of a 11-year beach profile dataset along 230 km of high-energy sandy coast. All morphological descriptors are characterized by a north-south gradient. Timing and magnitude of beach-dune recovery from the 2013-14 winter is variable. Shoreline change trends range from −5.9 m/year to +2.1 m/year. Post-winter beach-dune volume is a good proxy of shoreline change trend.